A astrofotografia lunar: uma ferramenta para o processo de ensino e aprendizagem de astronomia em uma interface com a geografia - Sant'Anna, Ana Claudia Santana Bomfim (2020)
The present work aimed to use Astrophotography in a geographical perspective, as a mediator of the teaching and learning process of phenomena related to the Moon. It was developed in Basic Education in a class of the 1st grade of High School, formed by 35 students aged 15 and 16 years old, from Colégio Estadual Maria Teófila - COMART, in the city of Amélia Rodrigues - BA. This work aimed to collaborate with the scientific divulgation in the aforementioned School Unit and, for that, the main methodological ways were chosen to observe the Moon with the naked eye, with a spyglass, telescope and systematic records, using the cell phone and the cell phone attached to the telescope. This research generated two educational products. A Didactic Sequence, entitled “The Moon”, through which a variety of activities were applied that supported the discussion of basic concepts of Astronomy, in particular, of our natural satellite; and another, an album of stickers with activities, called “Keeping an Eye on the Moon”, which took up, in a playful way, the concepts previously worked. Through the classroom discussions of all the activities developed during the process, it became evident that the observational practical classes with photographic records, using the cell phone, associated with the theoretical classes of Geography, are ratified as a methodology that, in fact, it stimulates and assists students in the understanding and construction of astronomical concepts, such as those studied in this research on the Moon.